Is the apple cubic? Reflections about gravity theories (REVISTA SAYWA, 2020)
Regarding the gravity description, the high school education in Colombia, and in many other countries, does not go beyond the Newton’s universal gravitation law, in most of the cases complemented with the story of Newton and the falling apple. One segment of this population know, additionally, that the most accepted gravity theory nowadays is Einstein’s general relativity, which generalizes the universal gravitation law. It is usual, therefore, that most of the people without a professional education in Physics associate the gravitation universal law, and as an extension general relativity, with the falling apple. Exploiting this association, this article discusses whether the apple might be cubic, i.e., whether there exists some description of the gravitational force that generalizes Einstein’s and that is well motivated and consistent with the most recent measurements
Keywords: Gravity; Newton; Einstein; Modify gravity